2014
DOI: 10.1002/cjce.22046
|View full text |Cite
|
Sign up to set email alerts
|

TGA and kinetic modelling of Co, Mn and Cu oxides for chemical looping gasification (CLG)

Abstract: Oxygen carriers for biomass gasification are capable of absorbing oxygen from air and desorbing it in the gasifier. Based on thermodynamic equilibrium, copper, manganese, and cobalt oxides have the highest oxygen release capacities among the different oxygen carriers. These oxygen carriers were deposited on alumina via incipient wetness impregnation. The weight loss of the CuO-Cu 2 O carrier, as measured in a thermogravimetric analyzer, was 10 % while it was 7 % for the Co 3 O 4 -CoO couple and only 3 % for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…On the other hand, X Red and t oc are related to each other according to the reaction rate expression [15]:…”
Section: Gasifiermentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, X Red and t oc are related to each other according to the reaction rate expression [15]:…”
Section: Gasifiermentioning
confidence: 99%
“…Aghabararnejad et al [15] compared the oxygen release capacity as well as oxidation, reduction rates of copper, cobalt and manganese oxides. They concluded that cobalt with 7 % of oxygen transport capacity has superior properties and can serve as an excellent oxygen carrier especially for solid fuel conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt has a moderate oxygen carrying capacity (7% of its weight) but the oxidation-reduction rates are 3 times greater and the thermal stability is superior compared to manganese and copper. Furthermore, experiments in a bubbling fluidized bed (7.8 cm ID, 2 m height) in the presence of biomass have shown that, sulfur has little effect on the cobalt oxide performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen is provided from cobalt oxide by reduction of Co 3 outlet. The experimental data were used to validate a kinetic based approach model.…”
Section: Introductionmentioning
confidence: 99%
“…It should possess excellent properties, including enough reactivity, high oxygen transfer capacity, low production cost, environmental friendliness, and a low tendency of fragmentation and attrition [8][9][10]. The main materials used as OCs are transition metal oxides, such as Mn3O4, Fe2O3, NiO, CuO, and CoO [11][12][13][14][15][16]. Among these metal oxides, Fe-based OC has been recognized as one of the most promising candidates, because it possesses the advantages of being low cost, having a good thermal stability, and being environmentally friendly [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%